2022
DOI: 10.1177/10225536221134032
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of primary shoulder dislocations requiring surgery: A cohort study from a major trauma center during 7 years

Abstract: Purpose The epidemiology of shoulder instability in the general population is lacking. The aim of the current study was to determine the incidence rate of primary shoulder dislocations requiring surgical interventions in a major trauma center within a large maintenance organization. Methods A retrospective cohort analysis of electronic health records database from 1 January 2014 and 31 December 2020 was conducted in major rural trauma center. This study included all patients aged 10 years or older with a prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous studies have shown similar but slightly lower rates of sports-related shoulder dislocations. 10 , 13 , 19 , 21 , 23 Men are more likely to dislocate their shoulders playing sports than women, who are more likely to dislocate their shoulders during nonsports-related activities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown similar but slightly lower rates of sports-related shoulder dislocations. 10 , 13 , 19 , 21 , 23 Men are more likely to dislocate their shoulders playing sports than women, who are more likely to dislocate their shoulders during nonsports-related activities.…”
Section: Discussionmentioning
confidence: 99%
“… 1,2 While surgical management is associated with lower rates of recurrence, 3 most people seem to prefer to avoid surgery after a first-time ASD. 4 Conservative management is also the initial treatment of choice by many athletes who wish to resume competitive participation within the same sporting season. 5,6 This choice is not without consequence as individuals following ASD exhibit fear of re-injury and fear of movement which often lead to avoidance behavior and a resultant lower quality of life.…”
Section: Background and Purposementioning
confidence: 99%